The global air pollution and undernutrition among children under five - Rozhan Khezri; Sepideh Jahanian; Mitra Gholami; Fatemeh Rezaei (Scientific Reports, 2025)
Abstract Malnutrition and PM2.5 pollution remain a pressing global public health concern, especially to vulnerable populations like children under five years old. This study aimed to investigate the correlation between undernutrition in children under five years old and air pollution (exposure to PM2.5) on a global scale. This ecological study evaluated the correlation between undernutrition (wasting and stunting) and air pollution in 123 countries. A multiple linear regression analysis was used to identify the factors significantly related to the wasting and stunting. The scatter plots were utilized to depict the prevalence of wasting and stunting in children under five years old across studied countries concerning air pollution, Human Development Index (HDI), and Socio-Demographic Index (SDI). The prevalence of wasting was higher in countries with higher exposure to PM2.5 (R2 = 0.13, p < 0.001), less HDI (R2 = 0.20, p < 0.001), and less SDI (R2 = 0.16, p = 0.005). Also, the prevalence of stunting was higher in countries with higher exposure to PM2.5 (R2 = 0.07, p = 0.003), less HDI (R2 = 0.54, p < 0.003), and less SDI (R2 = 0.52, p = 0.005). The results of multivariable linear regression indicated a direct and positive correlation between the prevalence of wasting in children under five years old and exposure to PM2.5 (β = 0.06, p = 0.003) and an indirect and negative correlation with HDI (β =-10.3, p < 0.001). Also, there was a significant association between the prevalence of stunting and HDI (β =-44, p < 0.003). There was a significant relationship between the prevalence of wasting in children under five years old and exposure to PM2.5 and HDI. Further research is required to confirm this association.